Measurements with the technical prototype for the Mu3e tile detector - Klingenmeyer, Hannah; Munwes, Yonathan; Briggl, Konrad; Zhong, Tiancheng; Chen, Huangshan; Shen, Wei; Schultz-Coulon, Hans-Christian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
The tile detector is a dedicated timing detector developed for the Mu3e experiment, which is designed to search for the lepton-flavour violating (LFV) decay μ→eee with a target sensitivity of 10−16. In order to determine the vertex and coincident time of the three decay electrons, precise spatial and timing measurements are necessary, resulting in the requirement of a time resolution below 100 ps for the tile detector. The tile detector, which is currently being developed at the Kirchhoff Institute for Physics, Heidelberg University, employs plastic scintillator tiles and silicon photomultipliers which are read out by dedicated 32-channel mixed signal readout ASICs. Measurements using the first technical prototype of the tile detector in two testbeam campaigns, undertaken at the Deutsches Elektron-Synchrotron (DESY) in Hamburg, Germany in February and June 2018, show a preliminary single channel timing resolution of about 47 ps, which is well below the required resolution of 100 ps. Furthermore, the production and assembly procedures for the final detector system were defined based on the experience gained from the construction of the prototype. Thermal simulation studies using the prototype provided additional input for the finalisation of the detector structure.
Available online 25 September 2019
Gesehen am 27.03.2020